First, distribute the -4 on the left side of the equation:
-4(2x - 11) = 12
-8x + 44 = 12
Next, subtract 44 from both sides to isolate the x term:
-8x = -32
Finally, divide both sides by -8 to solve for x:
x = 4
Therefore, x = 4.
Solve for x : -4(2x - 11) = 12
3 answers
SOLVE FOR X: -3(-4x -3) = 27
First, distribute the -3 on the left side of the equation:
-3(-4x - 3) = 27
12x + 9 = 27
Next, subtract 9 from both sides to isolate the x term:
12x = 18
Finally, divide both sides by 12 to solve for x:
x = 1.5
Therefore, x = 1.5.
-3(-4x - 3) = 27
12x + 9 = 27
Next, subtract 9 from both sides to isolate the x term:
12x = 18
Finally, divide both sides by 12 to solve for x:
x = 1.5
Therefore, x = 1.5.